De la monumentalisation à la théâtralité Essai sur l’enceinte urbaine en Italie centrale du VIIIe au Iers. av. J.-C - Fontaine, Paul 1954- (2022)
This article aims the ancient fortifications, looking at their monumentalisation and theatricality, using these modern concepts for better understandig of ancient practices. The focus is put on the city-walls of Central Italy from the 8th to 1st centuries BC. Ancient and modern meanings of “monument” are confronted to introduce an up-dated discussion on the relationship between monumentalisation of the fortifications and urban development in Preroman context. The theatricality of the city-walls, a growing phenomenon from the 3th century, takes on different forms for which are presented exemples from Etruria and Umbria.
Keywords: Ancient fortifications; monumentalisation; Urbanization; Architecture; Theatricality; Central Italy; Amelia; Perugia; Todi; Spoleto; Spello